Prevalence and determinants of acute respiratory infections among under-five children in a tertiary care center at Pokhara, Nepal - Poudel, Pramila; Soti, Harikala (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Acute respiratory infection (ARI) is a major determinant of morbidity and mortality among under-five children in developing countries. Despite decreasing trends in childhood morbidity and mortality, ARI remains a significant predictor of recurrent illness and hospitalization among under-five children in Nepal. This study was conducted to assess the prevalence and determinants of ARI among under-five children at a tertiary care center at Pokhara, Nepal.Methods: An analytical cross-sectional study was conducted among 358 mother-child dyads who were recruited through a purposive sampling technique and data was collected through the computer-assisted personal interview (CAPI) technique. Descriptive and inferential statistics were used. The level of statistical significance was set at p